Somatic Mutations of Hematopoietic Cells Are an Additional Mechanism of Body Aging, Conducive to Comorbidity and Increasing Chronification of Inflammation - Yegor E. Yegorov; Anastasia V. Poznyak; Evgeny E. Bezsonov; Alexander D. Zhuravlev; Nikita G. Nikiforov; Khava S. Vishnyakova; Alexander N. Orekhov (Biomedicines, 2022)
It is known that the development of foci of chronic inflammation usually accompanies body aging. In these foci, senescent cells appear with a pro-inflammatory phenotype that helps maintain inflammation. Their removal with the help of senolytics significantly improves the general condition of the body and, according to many indicators, contributes to rejuvenation. The cells of the immune system participate in the initiation, development, and resolution of inflammation. With age, the human body accumulates mutations, including the cells of the bone marrow, giving rise to the cells of the immune system. We assume that a number of such mutations formed with age can lead to the appearance of “naive” cells with an initially pro-inflammatory phenotype, the migration of which to preexisting foci of inflammation contributes not to the resolution of inflammation but its chronicity. One of such cell variants are monocytes carrying mitochondrial mutations, which may be responsible for comorbidity and deterioration in the prognosis of the course of pathologies associated with aging, such as atherosclerosis, arthritis, osteoporosis, and neurodegenerative diseases.